THE EFFECTIVENESS OF INTERACTIVE WRITING INSTRUCTION TOWARD HEARING IMPAIRED STUDENTS’ ABILITY IN WRITING SKILL AT SMALB-B KEMALA BHAYANGKARI 2 GRESIK - Safitri, Devi Ratna; Ma?rifah, Ulfatul (Jetlal, 2017)
The positive relationship between literacy on writing and phonological toward hearing impaired students in which the use of phonological information writing is important to produce a good composition in writing that indicated as a problem of hearing impaired student. Based on the previous studies, interactive writing instruction can be used for teaching learning writing especially for hearing impaired students. Further, the study suggests that it will be more effective if the researcher provides visual aids such as flash card an access for phonological information in a visual form. This study was designed to investigate the significant effect of interactive writing instruction toward hearing impaired students? ability in writing skill. The design of this study was pre experimental design in the form of one group pre-test and post-test design because only one subject was treated in this study. It means that, the study was done in one group only without other control group. The researcher chose students of first grade in SMALB-B Kemala Bhayangkari 2 Gresik. The data was collected by using test pre-test and post-test about announcement text. After getting the data, the researcher analyzed the data by using SPSS 16.00 and Wilcoxon Sign Rank test. The research finding showed that sign. (2-tailed) is .046. The sig. (2-tailed) was lower than 0.05 (0.04 < 0.05). Ho can be rejected because p value was above 0.05 that was 0.046 at 5% level. There was enough evidence to conclude that the use of interactive instruction on writing skill toward 5 hearing impaired students were significantly different. Therefore, the researcher suggests to English teacher for implementing of interactive writing instruction as an alternative strategy in English teaching. The researcher hopes for the further researcher to apply interactive writing instruction in other skills, and levels.